Capitalism, complexity, and polycrisis: toward neo-Gramscian polycrisis analysis - Michael J. Albert (Global Sustainability)
Abstract Non-technical summary Advocates of the concept of polycrisis show that our world faces many interconnected risks that can compound and reinforce each other. Marxist critics, on the contrary, argue that polycrisis advocates have not yet given sufficient attention to the role of capitalism as a root cause of these intersecting crises. This paper agrees with these critics. But I also argue that it is possible to develop an alternative approach to polycrisis analysis rooted in the traditions of Marxism and neo-Gramscian theory. The paper applies this approach to analyze the European Union's ongoing polycrisis and sketch out its possible futures.